Fast and Reproducible Vascular Neointima Formation in the Hamster Carotid Artery: Effects of Trapidil and Captopril - Matsuno, H; Stassen, J M; Hoylaerts, M F; Vermylen, J; Deckmyn, H (Thrombosis and Haemostasis, 1995)
Neointima formation was induced in the hamster carotid artery by mechanical intraluminal injury with a catheter covered with roughened dental cement. Neointimal thickening occurred as early as 7 days after denudation and further increased during the next 1 to 2 weeks. Proliferation indices of smooth muscle cells (SMCs) showed the highest proportion of proliferating cells in the media and neointima respectively 1 and 5 days after the vascular injury. Transmission and scanning electron microscopy of damaged carotid artery sections as well as immuno-histochemical stainings of von Willebrand factor (vWF) confirmed that reendothelialization was progressive and already complete on day 14, at which time the neointima formation was almost complete.In order to pharmacologically characterize this model further, the effects on neointima formation of trapidil (triazolopyrimidine), a platelet-derived growth factor (PDGF) antagonist, and captopril, an angiotensin converting enzyme inhibitor, were investigated. Trapidil administered orally twice daily at total doses of 25, 50 and 100 mg/kg/day, started 3 days prior to infliction of injury and up to 7 or 14 days after the catheterization, significantly reduced neointima formation. Captopril administered orally three times daily at a total dose of 100 mg/kg/day, equally reduced neointima formation, with 100 mg/kg/day trapidil being more effective than 100 mg/kg/day captopril 7 days after injury. When the treatment by either one of these drugs was arrested on day 7, neointima formation resumed quickly.The hamster appears to be a small, reproducible and fast model for the study of SMC proliferation, requiring only relatively small amounts of experimental drugs. The model furthermore is sensitive to substances known to reduce neointima formation in other animal models.